Computational functional analysis - Moore, Ramon E. (Ellis Horwood series in mathematics and its applications., 2007)
This course text fills a gap for first-year graduate-level students reading applied functional analysis or advanced engineering analysis and modern control theory. Containing 100 problem-exercises, answers, and tutorial hints, the first edition is often cited as a standard reference. Making a unique contribution to numerical analysis for operator equations, it introduces interval analysis into the mainstream of computational functional analysis, and discusses the elegant techniques for reproducing Kernel Hilbert spaces. There is discussion of a successful ''hybrid'' method for difficult real-life problems, with a balance between coverage of linear and non-linear operator equations. The authors successful teaching philosophy: ''We learn by doing'' is reflected throughout the book. Contains 100 problem-exercises, answers and tutorial hints for students reading applied functional analysisIntroduces interval analysis into the mainstream of computational functional analysis.